Opportunities and Challenges of Independent Nursing Practice: A Systematic Review - Hasibuan, Anisah; Nurhidayah, Rika Endah; Nasution, Siti Zahara (Universitas Muhammadiyah Surakarta, 2024)
Health services in the health professions can be used as business opportunities, building a culture of entrepreneurship and expanding professional roles into entrepreneurial health workers. Independent nursing practice is the practice of individual or group nurses in independent practice settings outside of health care facilities. Independent practice is a form of nursing that aims to standardise care for clients who need assistance because of ignorance, inability or unwillingness to meet their basic needs and care for themselves. Through the implementation of independent practice, nurses carry out their roles and functions in accordance with their authority. The purpose of this systematic review is to describe the opportunities and challenges of independent nursing practice. Methods: The research design used PRISMA systematic review. Journals were obtained from ProQuest and Google Scholar 2019-2023 database searches, full text, open access. Results: Based on the collected journals, independent nursing practice is a form of building an entrepreneurial culture and expanding professional roles to become entrepreneurial health workers. The motivation of nurses in independent practice is to improve the welfare of nurses, which can increase motivation. Nurses in independent practice face challenges because they are limited by the authority, responsibility and accountability that must be carried out in order to provide professional care.